Quantification of genetic diversity for drought adaptation in a reference collection of common bean (phaseolus vulgaris L.) - Simbarashe, Makunde Godwill (University of the Free State, 2013)
The aims of this study were to identify sources of drought tolerance in a common bean reference collection, to improve genetic and physiological understanding of drought tolerance in different gene pools of common bean, to establish the role of rooting characteristics in improving grain yield under drought conditions, to determine the genetic structure and diversity in the reference collection using SSR marker data, and to identify simply inherited markers in close proximity to genes affecting drought tolerance. Field experiments were laid out as 11x11 Mesoamerican and 9x9 Andean lattices with three replicates under irrigated and rainfed treatments at CIAT-Palmira and Harare Research Station. Yield was significantly correlated with total shoot biomass at mid pod fill, 100-seed weight, number of pods per plant and days to maturity under both treatments at both locations. Based on geometric means and drought sensitivity indices, BAT477, G11721, G4017, DOR390 (Mesoamerican) and SAB645, PVA1111, SEQ1003, SEQ1027, G17076 and G5142 (Andean) genotypes had high and stable yields across treatments in both locations and could serve as sources of drought tolerance in common bean. Two greenhouse experiments were conducted at CIAT-Palmira using the soil cylinder system, in a randomised complete block design with three replicates. Well watered and water stressed treatments were applied in each trial. In 2009 a total of 33 Andean landraces and three Mesoamerican checks were evaluated for deep rooting and other root properties. In 2010 phenotypic differences were determined between elite genotypes in root development under water stress. A total of 40 elite Andean and Mesoamerican genotypes commonly used as parents in many breeding programmes, were evaluated. Variability of root traits under water stress was expressed either as adaptive or constitutive traits depending on genotype. It was found that deep rooting alone may not be adequate for drought tolerance in common bean, as some deep rooted genotypes had poor yields under field conditions. SSR and SNP markers were used for molecular characterisation of the reference collection to determine the population structure and identify statistically significant marker-trait associations relevant for drought tolerance in the reference collection. The reference collection is strongly structured following the geographical origins of the genotypes. TOG896943-500, TOG918200- 347 and TOG 910860-634 were significantly associated with 100-seed weight and total shoot biomass across locations and treatments. In conclusion, all findings in the current study need to be integrated to develop drought tolerant common bean varieties in future. Mapping studies should be extended to candidate gene analysis for the identified marker-trait associations.

Die doelwitte van hierdie studie was om bronne van droogtetoleransie in ‘n algemene droëboon verwysingsversameling te bepaal, om die genetiese en fisiologiese begrip van droogtetoleransie in verskillende geenpoele van droëbone te verbeter, om die rol van worteleienskappe in die verbetering van saadopbrengs onder droogtetoestande te bepaal, om die genetiese struktuur en diversiteit in die verwysingsversameling met die gebruik van SSR merkerdata te bepaal, en om eenvoudig oorgeërfde merkers te identifiseer wat naby aan gene lê wat droogtetoleransie bepaal. Veldproewe is uitgelê as 11x11 Mesoamerikaanse and 9x9 Andiese vierkante met drie herhalings, onder besproeiings en droëlandtoestande by CIAT-Palmira en Harare Navorsingsstasie. Opbrengs was betekenisvol gekorreleer met totale bogrondse biomassa teen mid-peulvulstadium, 100-saadmassa, aantal peule per plant en dae tot volwassenheid onder beide behandelings by beide omgewings. Volgens geometriese gemiddeldes en droogtesensitiwiteitsindekse, het BAT477, G11721, G4017, DOR390 (Mesoamerikaans) en SAB645, PVA1111, SEQ1003, SEQ1027, G17076 en G5142 (Andiese) genotipes hoë en stabiele opbrengste oor die behandelings in beide omgewings getoon en kan dien as bronne van droogtetoleransie in droëbone. Twee glashuisproewe is by CIAT-Palmira uitgevoer waar die grond silindersisteem in ‘n gerandomiseerde blokontwerp met drie herhalings gebruik is. Optimale en water gestremde behandelings is toegepas in beide proewe. In 2009 is ‘n totaal van 33 Andiese landrasse en drie Mesoamerikaanse standaarde vir diep wortelvermoë en ander worteleienskappe geëvalueer. In 2010 is fenotipiese verskille tussen elite genotipes vir wortelontwikkeling onder waterstremming bepaal. ‘n Totaal van 40 elite Andiese en Mesoamerikaanse genotipes wat algemeen as ouers gebruik word in teelprogramme, is geëvalueer. Variasie in worteleienskappe onder waterstremming is as aanpassingseienskappe of samestelling van eienskappe uitgedruk. Daar is gevind dat die vermoë om diep wortels te vorm nie alleen genoeg is om droogtetoleransie in droëbone te verseker nie omdat sommige genotipes wat diep wortels kon vorm, swak opbrengste onder veldtoestande gehad het. SSR en SNP merkers is vir die molekulêre karakterisering van die verwysingsversameling gebruik om populasiestruktuur te bepaal en om statisties betekenisvolle merker-eienskap assosiasies relevant vir droogtetoleransie in die verwysingsversameling te bepaal. Die verwysingsversameling het ‘n baie duidelike struktuur volgens die geografiese oorsprong van die genotipes getoon. TOG896943-500, TOG918200-347 en TOG 910860-634 was betekenisvol met 100-saadmassa en totale bogrondse biomassa oor lokaliteite en behandelings geassosieer. Alle bevindings van hierdie studie moet geïntegreer word om in die toekoms droogtetolerante droëboonvariëteite te ontwikkel. Karteringsstudies moet uitgebrei word om kandidaat gene te analiseer en identifiseer vir merker-eienskap assosiasies.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2013
Keywords: Common beans